Jesse C. Rines papers - Rines, Jesse C.
Three journals (1863-1889) and daybook (1888-1890) relating to business accounts in Rines' blacksmith shop and general store. Includes miscellaneous fragments.
General storekeeper and blacksmith of Hampden, Me.
Collection material in English.
Keywords: Blacksmithing -- Maine; General stores -- Maine; Hampden (Me.) -- Commerce; Maine -- Commerce; Blacksmiths; Merchants